Study of Confinement Index of High-Strength Concrete Columns Reinforced with High-Strength Steel Bars - Agustiar, Agustiar; Tavio, Tavio; Putu Raka, I Gusti (IPTEK Journal of Proceedings Series, 2017)
Nowadays, the need of mega structures such high-rise buildings and long-span bridges due to the rapid growth of population is becoming increasingly urgent. The bigger the structures the higher the load should be carried by their structural members. To resist higher load, it normally requires larger size members. In reinforced concrete members, the capacity enhancement can be attained by either increasing the element size, the grade of materials used (concrete and steel bars), or the number or size of the steel bars used. However, higher-strength materials such as concrete and steel typically have more brittle properties. To improve the ductility of the concrete, it can be achieved by providing confining steel through transverse reinforcement. For higher-strength steel bars, a chemical based research has been conducted in recent years to come up with the high strength yet ductile steel material. This paper focuses on the analysis of various strengths of concrete columns 30 MPa and to 60 MPa reinforced and confined with high-strength reinforcing steel bars 550 MPa (Grade 80) with variety cross section of columns. From the study, it can be concluded that the confinement index decreases significantly with the increase of concrete strength. The use of higher-strength transverse steel increases the confinement index. The greater strengths of concrete used, the confinement ratio will be smaller at the same spacing.